Community Structure of Phytoplankton as Bioindicators of Water Quality in Kuwang Wae Coastal Waters, East Lombok, Indonesia - Ulfa, Baiq Maria; Karnan, Karnan; Japa, Lalu (Jurnal Biologi Tropis, 2026)
Phytoplankton play a crucial role as a primary producer in aquatic ecosystems and can be used as a bioindicator to assess water quality. Aquaculture activities in coastal areas have the potential to alter the phytoplankton community structure through changes in the physical, chemical, and biological characteristics of the aquatic environment. This study aimed to analyze the composition, abundance, community structure, and role of phytoplankton as a bioindicator of water quality in Kuwang Wae Coastal Waters, East Lombok Regency. A descriptive-exploratory method with purposive sampling was employed at three observation stations, namely the pond outlet, transition zone, and reference area. The observed parameters included species composition, abundance, diversity index, evenness index, dominance index, importance value, and water quality parameters. The reserch identified 72 species of phytoplankton belonging to five divisions: Chrysophyta, Dinophyta, Cyanophyta, Chlorophyta, and Euglenophyta. The species with the highest importance values were Gonyaulax spinifera, Bacteriastrum biconicum, Melosira sp., Chaetoceros brevis, and Bacteriastrum elongatum.  The average phytoplankton abundance was 1,614 ind/L, with variations among observation stations. The species diversity index ranged from 2.318 to 2.813, the species evenness index from 0.686 to 0.709, and the species dominance index from 0.130 to 0.174. Water quality of  Kuwang Wae Beach is still in relatively good, stable condition, and has not experienced significant ecological pressures. The results of this study are expected to provide baseline information for sustainable management, conservation, and monitoring of coastal water quality.